Analysis of Freedom of Speech and Human Rights - Winarno Budyatmojo; Itok Dwi Kurniawan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Indonesia's written constitution in the 1945 Constitution regulates the human rights of its citizens. One form of human right is the right to speak and express opinions. This article discusses the implementation of the right to freedom of speech and expression in national legal practice. This article was written using normative legal research methods with a conceptual approach and a statutory approach. The result of this research is that freedom of opinion is regulated and guaranteed by the constitution. The implementation of the right to freedom of expression is guaranteed by law and statute.